Copper sulfide-macroporous polyacrylamide hydrogel for solar steam generation. (2nd November 2019) - Sun, Yu; Gao, Jianping; Liu, Yu; Kang, Huiying; Xie, Minhui; Wu, Fuming; Qiu, Haixia
Graphical abstract: Highlights: During solar evaporation, a heating zone is formed at the air-water interface. The solar steam generation device has been optimized comprehensively. Solar photothermal conversion efficiency reached 92%. The solar steam generation device shows excellent reusability and performance stability. Abstract: The use of abundant solar energy to produce clean water by a solar steam generation device is a promising strategy to solve the long-term water and energy shortage. The development and application of photothermal materials are an effective way to improve solar photothermal conversion efficiency of the device. Herein, an inorganic-organic light-absorbing material, copper sulfide-macroporous polyacrylamide hydrogel (CuS-m-PAM), is reported for the first time. The CuS-m-PAM was prepared by in-situ synthesis method via loading CuS nanoparticles into macroporous polyacrylamide hydrogel (m-PAM). CuS-m-PAM forms a heating zone at the air-water interface and CuS nanoparticles can efficiently convert the strongly absorbed light into localized heat, thus reducing the heat loss in the transfer process. The results demonstrate that the solar photothermal conversion efficiency of CuS-m-PAM-0.05 is the highest and can reach 92% under one sun illumination (1000 W m −2 ). The rough surface of m-PAM and the plasma resonance effect of CuS nanoparticles improve the absorb ability to sunlight. The open macroporous structure of m-PAM also makes a great contribution to the water vapor escape of solar steam generation device. Moreover, the formation of N-Cu bond in CuS-m-PAM makes CuS nanoparticles more stabilization, and the solar photothermal conversion efficiency of CuS-m-PAM-0.05 remains 87.5% after 50 cycles of tests. CuS-m-PAM, as a novel light-absorbing material, can comprehensively optimize the solar steam generation device in light absorption, thermal insulation, water replenishment and steam exhaust, and thus provides a new practical method for maximum utilization of solar steam generation device.